2014
DOI: 10.1002/hed.23603
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and voice assessment in patients with early-stage glottic cancer

Abstract: In this cross-sectional study, voice quality, emotional functioning, and social contact were better in the RT group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 23 publications
3
29
0
Order By: Relevance
“…From the literature, 2 studies aimed at investigating QOL in patients with early glottic cancers using the QLQ‐H&N35 . Arias et al reported that social contact was significantly better (4.6 vs 12.1; P = .009) from patients who underwent RT than those who underwent TLM.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…From the literature, 2 studies aimed at investigating QOL in patients with early glottic cancers using the QLQ‐H&N35 . Arias et al reported that social contact was significantly better (4.6 vs 12.1; P = .009) from patients who underwent RT than those who underwent TLM.…”
Section: Discussionmentioning
confidence: 99%
“…From the literature, 2 studies aimed at investigating QOL in patients with early glottic cancers using the QLQ‐H&N35 . Arias et al reported that social contact was significantly better (4.6 vs 12.1; P = .009) from patients who underwent RT than those who underwent TLM. However, a similar study done by Laoufi et al reported that subscales of speech (4.51 vs 5.25; P = .04) and feeling ill (1.07 vs 1.22; P = .05) were different instead of social contact .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations